PERAN MANAJEMEN SARANA DAN PRASARANA TERHADAP EFEKTIVITAS PEMBELAJARAN DI UPTD SD NEGERI PALSATU - stevica tefbana; Hiwa Wonda; Mersi Hawu Haba; Joi Stevani Rohi (STKIP Subang, 2025)
This study aims to determine the role of facilities and infrastructure management in supporting learning effectiveness at UPTD SD Negeri Palsatu. This research uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and questionnaires distributed to teachers and school staff. The results showed that the management of facilities and infrastructure at the school has been implemented properly, starting from planning, procurement, maintenance, and utilization of learning facilities. Adequate facilities and infrastructure have a positive impact on the comfort, motivation, and effectiveness of the learning process. In addition, collaboration among the principal, teachers, staff, and the community plays an important role in maintaining the sustainability of school facility management. Thus, good facilities and infrastructure management has been proven to improve learning quality and overall educational outcomes in elementary schools.